Tes Toleransi Glukosa Oral pada Ibu Hamil Trimester II Dan III di Puskesmas Rajabasa Bandar Lampung - Nada Irmilia Sari; Fonda Octarianingsih; Festy Ladyani; Bambang Kurniawan (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Gestational Diabetes Mellitus (DMG) is the intolerance of blood glucose levels during pregnancy. One method that can be done to help diagnose diabetes mellitus is by conducting an oral consent approval (TTGO) test. Description of Oral Glucose Tolerance Tests in second and third trimester pregnant women at the Rajabasa Health Center in Bandar Lampung City in 2020. This research method uses descriptive research. The sampling technique using the total sampling method obtained a total sample of 30 samples. Test results for trimester II and III pregnant women as many as 30 respondents had GDP <95 mg/dl and TTGO <125mg / dl (100%). Age <35 years as many as 15 people (100%) and 14 people (93.3%). Second trimester BMI is normal as many as 13 people (86.7%) and third trimester 14 people (93.3%), statistic parity of trimester II and III pregnant women are primipara as many as 7 people (46.7%). had a normal blood pressure of 14 people (93.3%), and 13 people (86.7%). Performing an Oral Glucose Tolerance Test (TTGO) on pregnant women can help improve maternal safety both during pregnancy and pregnancy.